Mendelian randomization suggests a causal relationship between gut dysbiosis and thyroid cancer - Zhu, Feng; Zhang, Pengpeng; Liu, Ying; Bao, Chongchan; Qian, Dong; Ma, Chaoqun; Li, Hua; Yu, Ting (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Alterations in gut microbiota composition and function have been linked to the development and progression of thyroid cancer (TC). However, the exact nature of the causal relationship between them remains uncertain.A bidirectional two-sample Mendelian randomization (TSMR) analysis was conducted to assess the causal connection between gut microbiota (18,340 individuals) and TC (6,699 cases combined with 1,613,655 controls) using data from a genome-wide association study (GWAS). The 2 primary analysis used the inverse-variance weighted (IVW) method to estimate the causal effect, with supplementary approaches including the weighted median, weighted mode, simple mode, and MR-Egger. Heterogeneity and pleiotropy were assessed using the Cochrane Q test, MR-Egger intercept test, and MR-PRESSO global test. A reverse TSMR analysis was performed to explore reverse causality.Results: This study identified seven microbial taxa with significant associations with TC.